2021
DOI: 10.1177/01939459211005712
|View full text |Cite
|
Sign up to set email alerts
|

Job Characteristics, Emotional Exhaustion, and Work–Family Conflict in Nurses

Abstract: The purpose of this study is to identify whether emotional exhaustion, a component of burnout, mediates the relationship between job demands, job resources, and work–family conflict (WFC). A cross-sectional design was used with survey data. A total of 1,202 nurses in eastern Canada participated in this study. Data were collected via an online survey and analyzed using mediation analysis. The results indicated that job demands and emotional exhaustion predicted WFC. Moreover, emotional exhaustion partially medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 62 publications
1
8
0
1
Order By: Relevance
“…In our study, women had higher burnout than did men. Inconsistent with our study results, some studies do not show a difference in burnout by gender [ 6 ]. The proportion of male nurses is about 5% in Korea, 12% in the United States [ 25 ], 9% in Canada [ 26 ], and 8% in New Zealand [ 27 ]; that is, the proportion of male nurses worldwide is low.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, women had higher burnout than did men. Inconsistent with our study results, some studies do not show a difference in burnout by gender [ 6 ]. The proportion of male nurses is about 5% in Korea, 12% in the United States [ 25 ], 9% in Canada [ 26 ], and 8% in New Zealand [ 27 ]; that is, the proportion of male nurses worldwide is low.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown an association between work–family conflict (WFC) and burnout, particularly pertaining to emotional fatigue, in nurses [ 5 ]. Nurses may experience burnout due to WFC, as it threatens positive resources, such as their psychological and physical health [ 6 , 7 ]. Greenhaus and Beutell [ 8 ] extended the theory of roles to define WFC as a form of role conflict that occurs when the burdens and responsibilities of work and family are incompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, parece ser que cuando en el conflicto se encuentra comprometida la familia o el conflicto es de tipo inter -rol, la visión de intranquilidad se reduce, aceptando la responsabilidad por ella, sin embargo, cuando se encuentran involucrados aspectos de la vida laboral, es más productivo encontrar las descripciones de su salud en aspectos que no tengan nada que ver con su responsabilidad. (24,25) En estas situaciones, las competencias internas se interrelacionan como un anhelo de realizar cualquier competencia que tienda a disminuir la advertencia que aparenta una situación.…”
Section: El Desacuerdo Existente Entre El Trabajo Y La Familia Como G...unclassified
“…Existing research spotlights cognitive demands of flexible work (Allen et al., 2013; Allvin et al., 2011; Uhlig et al., 2022) and their relationship with employee well‐being (Meyer & Hünefeld, 2018), but their effects on work–home outcomes have not yet been sufficiently studied (Kubicek et al., 2022). In health care, research shows that specific job demands, like cognitive or interactional demands, can both be an antecedent of work–home conflict (Rhéaume, 2022) and a source of work–home enrichment (Solat et al., 2020). More precisely, Webster and Adams (2020) showed that challenge demands – demands that are difficult to overcome but hold the potential for learning and growth (e.g.…”
Section: Introductionmentioning
confidence: 99%